On the Geography of Trade: Distance is Alive and Well - Carrere, Celine (World Bank, Washington, D.C., 2013)
It has been widely argued that, with the decline in trade costs (for example, transport and communication costs), the importance of distance has declined over time. If so, this would be a boon for countries located far from the main centers of economic activity. The authors examine the evolution of countries' distance of trade (DOT) from 1962-2000. They find that the DOT falls over time for the average country in the world, and that the number of countries with declining DOT is close to double those with increasing DOT. Thus, distance has become more important over time for a majority of countries. The authors examine various hypotheses to explain this phenomenon. One conclusion is that the evolution of the DOT is unrelated to that of the overall trade costs but depends on the relative evolution of its components. The authors also examine the impact on the DOT of changes in production, customs, and domestic transport costs; air relative to land and ocean transport costs; competition, exchange rate policy, regional integration, uneven growth, and counter-season trade; and just-in-time inventory management. An interesting finding is that, though regional integration has a negative impact on the DOT, the countries forming trade blocs had a DOT that was growing faster or falling more slowly than that of excluded countries. The authors also offer some insights into how these changes may affect the home bias in consumption and the border effect.